Farmer Group Members' Absorption of Agricultural Extension with Demonstration Methods and Lectures (Case Study in Gunungrejo Village, Kedungpring District, Lamongan Regency) - Emmy Hamidah; Endang Tri Wahyurini; Agung Setyarini; Septina Elida (Postgraduate, University of Mataram, 2024)
The development of food crop agriculture helps the role of agricultural extension workers, maintains the stability of food self-sufficiency, increases people's income, and improves nutritional conditions through diversification of food types. Research objectives: to determine the absorption of members of the Berkah Tani I and Berkah Tani II farmer groups to counseling using demonstration methods and lectures; to determine differences in the absorption of members of Berkah Tani I and Berkah Tani II farmer groups to counseling using demonstration methods and lectures from various age strata. Hypotheses proposed: there are differences in the absorption of Berkah Tani I and Berkah Tani II farmer groups towards counseling using demonstration methods and lectures in each group; there are differences in absorption at each age level towards the use of demonstration methods and lecture methods. Data analysis methods using tabulation, scored and to determine the absorption at various age levels used the F test. The conclusions of the study are as follows: the use of demonstration method and lecture method in extension activities carried out alone - alone can improve the knowledge of farmers, among others: in Berkah Tani I farmer group that uses the demonstration method from the criteria enough (average value - average 27.52) to good (average value - average 40.78); in Berkah Tani II farmer group.